2008
DOI: 10.1002/ijc.23748
|View full text |Cite
|
Sign up to set email alerts
|

Variation in lung cancer risk by smoky coal subtype in Xuanwei, China

Abstract: Lung cancer rates in Xuanwei County have been among the highest in China for both males and females and have been causally associated with exposure to indoor smoky (bituminous) coal emissions that contain very high levels of polycyclic aromatic hydrocarbons. There are numerous coal mines across the County. Although lung cancer risk is strongly associated with the use of smoky coal as a whole, variation in risk by smoky coal subtype has not been characterized as yet. We conducted a population-based case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
90
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 25 publications
3
90
0
Order By: Relevance
“…concluded that the excess risk of lung cancer death for a worker exposed to 100 μg/m 3 for 45 years was approximately 1.5 times that of if they had not been exposed. 21 Not only are these values far in excess of what is reported in the current paper, the risk estimate associated with this level of exposure is insufficient to explain the difference in lung cancer rates between smoky and smokeless coal users (where the risk of lung cancer among smoky coal users can be up to 100 times that of smokeless coal users 22 ). We should note however, that occupational exposure limits and surveys may not be fully applicable to the situation in Xuanwei and Fuyuan, as exposure is lifelong and continuous throughout much of the day, compared to occupational exposure which only occurs during working hours in adult life.…”
Section: Discussionmentioning
confidence: 56%
“…concluded that the excess risk of lung cancer death for a worker exposed to 100 μg/m 3 for 45 years was approximately 1.5 times that of if they had not been exposed. 21 Not only are these values far in excess of what is reported in the current paper, the risk estimate associated with this level of exposure is insufficient to explain the difference in lung cancer rates between smoky and smokeless coal users (where the risk of lung cancer among smoky coal users can be up to 100 times that of smokeless coal users 22 ). We should note however, that occupational exposure limits and surveys may not be fully applicable to the situation in Xuanwei and Fuyuan, as exposure is lifelong and continuous throughout much of the day, compared to occupational exposure which only occurs during working hours in adult life.…”
Section: Discussionmentioning
confidence: 56%
“…5, 6 Constituents of smoky coal and its emissions have been explored in an attempt to pinpoint those that account for lung cancer risk. 710, 25, 26 Here, we integrated untargeted adductomics with external exposure measurements to investigate the influence of fuel type and external exposures on downstream biological processes that are reflected by Cys34 adducts.…”
Section: Discussionmentioning
confidence: 99%
“…13, 14 However, the heterogeneity of emissions of PAHs and other combustion products, even across subtypes of smoky coal has complicated analysis of exposure-response relationships. 710 …”
Section: Introductionmentioning
confidence: 99%
“…The primary source of indoor air pollution in Xuan Wei is smoke from domestic fuel combustion for heating and cooking with most residents burning smoky coal (bituminous coal) and some using smokeless coal (anthracite coal). Smoky coal use in Xuan Wei homes is associated with very high and comparable risks of lung cancer in both men and women (7,8).…”
Section: Introductionmentioning
confidence: 99%